Nivel cognitivo y riesgos en el uso de equipos de protección personal en prácticas académicas de estudiantes de la Facultad de Agronomía - Loayza Torres, Diana Carolina (2024)
The use of Personal Protective Equipment (PPE) is essential for preventing accidents and protecting health in academic and professional activities involving physical risks. This study aims to evaluate the cognitive level of students from the Faculty of Agronomy at the National University of the Peruvian Amazon regarding the proper use of PPE and the risks associated with its incorrect use during academic practices. Furthermore, it identifies key factors influencing adherence to PPE use, highlighting the impact of cognitive understanding and safety culture within the academic environment. The results reveal that inadequate training and supervision contribute to risky behaviors among students. This research contributes to the existing literature by addressing a critical aspect of safety in academic practices, emphasizing the importance of knowledge and awareness in reducing risks, and proposing strategies to improve PPE use in the training of future agronomy professionals.